Refractive errors in children: analysis among preschool and school children in Tuzla city, Bosnia and Herzegovina - Amra Nadarević Vodenčarević; Meliha Halilbašić; Anis Međedović; Vahid Jusufović; Adisa Pilavdžić; Aida Drljević; Mufid Burgić (Medicinski glasnik, 2020)
Aim: To establish the prevalence of refractive errors in preschool and school children between 4 and 15 years of age, living in Tuzla, Bosnia and Herzegovina. Methods: Children from all elementary schools in the city of Tuzla and as well from eight day-care centres were screened for refractive errors in the period 2015-2019. Any child, who failed to pass the screening examination, was referred to an ophthalmologist for complete ophthalmological evaluation. The obtained data were analysed using non-parametric statistics. Results: The highest number of children who were tested after the screening process was during 2015. A total of 7415 children (3790 males and 3625 females), in the age range of 4-15 were screened. In the total sample of children who were completely evaluated (n=145; 290 eyes) the most common refractive error was astigmatism, in 152 (52.4%) eyes. In the preschool children (n=18; 36 eyes), the most common refractive error was astigmatism, in 19 (52.8%) eyes, followed by hyperopia, in 9 (25%) eyes. In the school children (n=127) (254 eyes), the most common refractive error was astigmatism, in 133 (52.4%) eyes, followed by myopia, in 92 (36.2%) eyes. The overall prevalence of refractive errors was 1.95% (145 with refractive error out of 7415 screened). Conclusion: Prevalence of refractive errors is high enough to justify a school eye screening programme.
Keywords: astigmatisms; hypermetropia; myopia; visual screening